A Study of Syntactic Errors in English Produced by Non-Native Speakers Using Social Media Platforms - Novriyani; Rizki Anugrah PR (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The study investigated syntactic errors in English produced by non-native speakers using social media platforms. To collect the data, the researcher analyzed based on the students’ opinions in Whatsapp group. The partcipants of the research were the students of Islamic Institute Darul A’mal Lampung. There were 15 participants of English Education Department. The results showed that there were 15 syntactic errors based on their chatting. Syntactic error could be caused by intralingual factors, which are limited vocabulary knowledge, weak grasp of English grammar, sentence structure mistakes, punctuation errors, and confusion about different types of clauses. To reduce students' sentence errors, teachers can increase students' awareness of the differences between first and second language rules. Additionally, it is recommended that teachers explicitly teach sentence types and common sentence errors through sentence combination tasks. These strategies can be effectively implemented if teachers use engaging teaching methods and techniques.